2006
DOI: 10.1590/s0102-311x2006000500002
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and gastric cancer: systematic review and meta-analysis

Abstract: USA, for the five Japanese studies, for the six studies from Europe,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 56 publications
2
32
2
1
Order By: Relevance
“…Previous case-control and cohort studies that investigated the association between coffee consumption and gastric cancer risk by gender, reported no significant associations. 30 Hence, the observed heterogeneity by gender may well be explained by chance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case-control and cohort studies that investigated the association between coffee consumption and gastric cancer risk by gender, reported no significant associations. 30 Hence, the observed heterogeneity by gender may well be explained by chance.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine, kahweol, and cafestol in coffee may contribute to a protective effect against cancer [68]. Based on the evaluation of two prospective and eight casecontrol studies, which showed no statistically signifi cant association between coffee consumption and gastric cancer, the WCRF/AICR concluded that high consumption of coffee "probably" has no relation with the risk of gastric cancer [3].…”
Section: Black Tea and Coffeementioning
confidence: 99%
“…Based on the evaluation of two prospective and eight casecontrol studies, which showed no statistically signifi cant association between coffee consumption and gastric cancer, the WCRF/AICR concluded that high consumption of coffee "probably" has no relation with the risk of gastric cancer [3]. In a more recent systematic review and meta-analysis of 23 studies (7 cohort studies and 16 case-control studies) [68], coffee intake showed no effect on gastric cancer when all studies were combined (OR = 0.97, 95% CI = 0.86-1.09), with a combined risk estimate of 1.02 (95% CI = 0.76-1.37) for cohort studies, 0.90 (95% CI = 0.70-1.15) for population-based casecontrol studies, and 0.97 (95% CI = 0.83-1.13) for hospital-based case-control studies. Notwithstanding that risk estimates differed signifi cantly according to country of origin, with North American studies presenting a signifi cantly higher risk, this meta-analysis showed no overall effect of coffee consumption on gastric cancer risk.…”
Section: Black Tea and Coffeementioning
confidence: 99%
“…Finally, we included 80 papers for this overview of reviews, but in our article we only reviewed 55 etiological SRs/meta-analyses (Fu et al, 1995;Huang et al, 1998;Jacobs et al, 1998;Danesh et al, 1999;Eslick et al, 1999;Jia et al, 2000;Wu et al, 2000;Xue et al, 2001;Huang et al, 2003;Guo et al, 2004;Li et al, 2004;Botelho et al, 2006;Hu et al, 2006;Jakszyn et al, 2006;Liu et al, 2006;MacLean et al, 2006;Nishino et al, 2006;Tian et al, 2006;Xu et al, 2006;An et al, 2007;Kubo et al, 2007;Lunet et al, 2007;Merrill et al, 2007;Bae et al, 2008;Ladeiras-Lopes et al, 2008;Kuoppala et al, 2008;Shimazu et al, 2008;Zhou et al, 2008;Huang et al, 2009;La Torre et al, 2009;Mulholland et al, 2009;Myung et al, 2009;Yang et al, 2009;Zhang et al, 2009;Cavaleiro-Pinto et al, 2010;Gatto et al, 2010;Hussein et al, 2010;Kang et al, 2010;Kim et al, 2010;…”
Section: Search Resultsmentioning
confidence: 99%